The Continentalist Classic: Joseph Kinsey Howard's Strange Empire, Louis Riel, and Canada. Issue 2 (2nd April 2020) - Braz, Albert
ABSTRACT: One of the many ironies about the Métis political leader, poet, and mystic Louis Riel (1844–1885) is that the most influential book written about him is not by a Canadian, much less a Métis, but by an American. The popularity among Canadian writers and visual artists of Joseph Kinsey Howard's Strange Empire: A Narrative of the Northwest (1952) is puzzling, since Howard makes little effort to camouflage his support of US expansion into North America's northern plains and north. Equally curious, by the end of his book, Howard disowns Riel and embraces his Saskatchewan commander Gabriel Dumont as the real "prince of the prairies." The most plausible explanation for the appeal of Strange Empire to Canadians is that, by focusing on the Canada-US dimension of the Riel conflicts, even an unapologetic US continentalist like Howard concedes that Canada somehow emerged victorious over its powerful neighbor.